The Medical Tourism Development Possibilities in the Eurasian Space - S. L. Mozokina; V. A. Plotnikov (Евразийская интеграция: экономика, право, политика, 2023)
The article discusses the features of the organization of sanatorium-resort complexes of the Russian Federation and the countries of the Commonwealth of Independent States (CIS). The positive impact of the development of sanatorium-resort service systems on the preservation and development of human capital was noted. The authors analyze the possibilities and development trends of medical and health, including sanatorium-resort, tourism in Russia and in the territory of the CIS participating countries.Aim. To determine the potential and promising directions for the development of health tourism (including sanatorium and medical) in the Eurasian space.Tasks. To consider the stages of development of health and wellness tourism (including health, spa and medical) in Russia and the CIS member countries, to study the current state of the spa complex and natural healing resources in Russia and the CIS member countries, to analyze tourist flows in the Eurasian space.Methods. The study used statistical data obtained from open sources, such as the Unified Interdepartmental Information and Statistical System, the official website of the Federal Agency for Tourism, the official websites of government agencies of the member countries of the Commonwealth of Independent States, etc. sources. Standard scientific methods of analysis and synthesis, expertanalytical, structural-logical, modeling and forecasting methods were used to process the obtained initial data.Results. The study showed that for integration in the field of health and wellness and sanatoriumresort tourism, it seems to us expedient to create a single information portal that combines information about natural healing resources, sanatorium-resort organizations, their profile, material and technical base and accommodation conditions (possibly with a booking function). This will create an information technology basis for further integration in the field under consideration. Within the framework of the same direction, the authors recommend taking measures to harmonize the forms and procedures for obtaining documents for sanatorium treatment (sanatorium cards), including electronic ones. Due to the fact that, subject to further development of integration processes in the considered area, the issue of staffing will become acute, in connection with which the authors propose to develop network master’s programs on the organization and management of health tourism (including medical tourism and sanatorium tourism), implemented on the basis of universities of the member countries of the Commonwealth of Independent States. At the same time, it is supposed to include in the competence of network master’s programs such competencies as knowledge of the profiles of sanatoriums, natural healing resources, balneology, the ability to use digital platforms in work.Conclusions. During the period of “post-normality”, under the influence of the anti-Russian sanctions policy of the “collective West”, prerequisites arise for closer integration of the CIS countries in the field of health and wellness (including wellness, sanatorium and medical) tourism. In order to facilitate integration processes, it is proposed to create a single digital platform, unify information technology support, as well as develop network educational programs for the training of specialized personnel.